2002
DOI: 10.1046/j.1365-8711.2002.05561.x
|View full text |Cite
|
Sign up to set email alerts
|

Sakurai's Object (V4334 Sgr): evolution of the dust shell from 1999 to 2001

Abstract: We present fits to 1–5 μm spectra of the dust shell around Sakurai's Object (V4334 Sgr) obtained over the period 1999 May to 2001 September, using the dusty modelling program. We find that the emission is consistent with carbon dust grains for which the optical properties are predominantly graphitic, and for which sizes range from ∼0.005 to ∼1–2 μm with a size distribution n(a) da∝a−3 da. We further find an increase in the mass‐loss rate, and in the angular diameter of the dust shell, which may now be resolvab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…From Table 1 we see that 0 2 ± 0.2, indicating that the dust flux at 2.3 µm is 9.4 × 10 −12 W m −2 µm −1 . This is much higher than in later spectra, when the star had become completely obscured and the dust emission dominated the overall spectrum (Tyne et al 2002). At later times ( > ∼ 1999) the dust envelope expanded and cooled and the peak of its spectrum shifted to longer wavelengths.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…From Table 1 we see that 0 2 ± 0.2, indicating that the dust flux at 2.3 µm is 9.4 × 10 −12 W m −2 µm −1 . This is much higher than in later spectra, when the star had become completely obscured and the dust emission dominated the overall spectrum (Tyne et al 2002). At later times ( > ∼ 1999) the dust envelope expanded and cooled and the peak of its spectrum shifted to longer wavelengths.…”
Section: Discussionmentioning
confidence: 70%
“…The effect of circumstellar dust Pavlenko & Geballe (2002) have shown that the 2 µm spectral region of V4334 Sgr is affected by emission from the hot dust known to envelop V4334 Sgr at this time, and which most likely formed at some 20 stellar radii from the stellar atmosphere Tyne et al 2002). The dust shell first appeared in 1997 March and, by 1998 August, its presence was well established photometrically (Kerber et al 1999; and spectroscopically (Tyne et al 2000(Tyne et al , 2002. The dust emission veils the CO absorption lines, and to estimate its effect we suppose that the dust emission adds some continuum flux in our spectral region, effectively reducing the residual fluxes r ν = F …”
Section: Letter To the Editormentioning
confidence: 99%
“…The equilibrium temperature dust at the radius determined in is ∼100 K. This is based on assumptions of 1 μm graphitic carbon grains (Tyne et al 2002); a stellar luminosity of 3000 L ⊙ (Herwig 2001; Tyne et al 2002) and an effective temperature of 5200 K (Pavlenko 2002). An equilibrium temperature of 320 K at this radius would require an impossibly high luminosity; a factor of >100 greater than predicted by the models of Herwig (2001) and Tyne et al (2002). The CO temperature of 320 K is also inconsistent with stellar radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The emission feature noted by Lynch et al either may have been an artefact of data reduction (which Lynch et al state is unlikely), or its carrier is no longer present, or (in our opinion the most likely explanation) the 1000 K blackbody assumed by Lynch et al was not a good approximation to the dust continuum (see below). Tyne et al (2002) have modelled the dust emission from V4334 Sgr and in principle we could use similar modelling to define the continuum for our 8-13 µm observation. However at present we have no other constraints on the dust emission and, for the purpose of extracting the profile of the silicate feature, we attempt two alternative fits to the dust continuum over the wavelength ranges 8-8.7 µm and 12.1-12.8 µm (i.e.…”
Section: The Extinction In the Silicate Featurementioning
confidence: 99%
“…V4334 Sgr is currently enveloped in a carbon-rich dust shell that is optically thick in the visual and near-infrared (Tyne et al 2002). Before it was obliterated by the dust shell, the underlying star was also determined to be carbon-rich (Asplund et al 1997).…”
Section: Circumstellar Silicate?mentioning
confidence: 99%